Exemplary Youth Leadership Series: Model the Way - Megan Stein (EDIS, 2019)
This publication series is designed to outline strategies and experiences to expose youth to and engage them with leadership concepts. In this series, activities have been developed to introduce youth to Kouzes and Posner?s five practices of exemplary leaders. This new 2-page article allows students to engage with the first practice: modeling the way. Leaders must identify and exemplify values in order to be effective. The two outlined activities help students illustrate the idea of identifying values and modeling expectations. Written by Megan Stein and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc346